Correlations between the stress paths of a monotonic test and a cyclic test under the same initial conditions - Li, Yao; Yang, Yunming; Yu, Hai-Sui; Roberts, Gethin (Elsevier, 2017)
In most experimental studies on liquefaction, cyclic loadings are applied on specimens with various initial conditions. However, few studies compared cyclic test results with monotonic results under the same initial conditions. The relation between monotonic tests and cyclic tests is crucial for understanding liquefaction mechanics and liquefaction resistance. This work compares the stress paths of a monotonic test with those of a cyclic test under the same initial conditions, and concluded that the stress path of monotonic tests envelops the stress path of cyclic tests under the same initial conditions. In addition, a new parameter, Level of Liquefaction Index (LI) is proposed to evaluate the liquefaction resistance of specimens under various initial conditions, and a linear relationship between LI and number of cycles at failure is found.